Growth Analysis of Caulerpa lentillifera Cultivated at Laboratory Scale with Different Light Intensities - Fisma Josara Apriliyanti; Yenny Risjani; Asus Maizar Suryanto Hertika; Akhsan Fikrillah Paricahya (Jurnal Penelitian Pendidikan IPA, 2024)
In Indonesia, Caulerpa sp. is often utilized as an edible food ingredient by eating it raw as a vegetable salad or as a vegetable. Different light intensities greatly affect the growth of sea grapes (Caulerpa lentillifera). However, this type of seaweed is still few who can cultivate it. Therefore, the purpose of the study was to analyze the growth performance of Caulerpa lentillifera seedlings at the cultivation stage in the laboratory with different light intensities. The research was conducted using the RAL method with 5 treatments and 4 replications. Light intensity (1,000, 2,000, 3,000, 4,000, 5,000 Lux) was applied during cultivation. The specific growth rate ranged from 0.0065%/day - 0.0061%/day. The number of ramuli of Caulerpa lentillifera ranged from 651 grains - 723 grains. The number of tallus Caulerpa lentillifera during 45 days of maintenance with various treatments ranged from 28 branches - 32 branches. The conclusion of this research is that light intensity significantly affects the growth of Caulerpa lentillifera.